Communication and Healthcare: Self-Reports of People with Hearing Loss in Primary Care Settings. Issue 5 (20th October 2019) - Stevens, Madelyn N.; Dubno, Judy R.; Wallhagen, Margaret I.; Tucci, Debara L.
ABSTRACT: Objectives : To assess the experiences of people with hearing loss in healthcare environments to characterize miscommunication and unmet needs, and guide recommendations for improving outcomes and access. Methods : Anonymous survey developed by subject-matter experts was posted on a large national hearing-loss consumer and advocacy organization website and email listserv. Data were collected and managed via RedCAP. Results : Responses were received from 1581 individuals. Respondents reported moderate or significant difficulty communicating with all listed providers. Three communication situations emerged as often presenting communication difficulties: hearing one's name when called in the waiting room, hearing when the speaker's back was turned, and hearing when communicating by telephone. Despite 93% of respondents indicating they sometimes or often let providers know about their hearing loss, 29.3% of all respondents still reported that no arrangements were made to improve communication. Conclusions : This study clearly demonstrates the ongoing difficulties faced by individuals with hearing loss, particularly older adults, as they attempt to navigate both providers and situations associated with a typical primary care office visit. Clinical Implications : Inexpensive and efficient changes to improve communication include (1) Improving one-on-one provider communication by facing the individual with good lighting, clear speaking, and not obstructing one's mouth; (2) Environmental changes such as using visual or tactile alerting devices in waiting rooms and adding noise-dampening carpeting and curtains; and (3) Avoiding telephones and conveying health information in writing.